Dinamika Migrasi Desa Kota di Indonesia: Karakteristik dan Kehidupan Migran Baru di Tangerang, Propinsi Banten - Fina Itriyati (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2015)
This paper attempts to examine the dynamics of recent migration in Tangerang city, the major industrial city on the outskirts of Jakarta. In this paper we fist deal with migration patterns associated with economic and social change in Indonesia, both historically and in more recent times especially in Tangerang city. The fild research conducted both in Tangerang city and Tangerang district in 2008 and as part of collaborative research on rural urban migration in Indonesia. Using data gathered from household urban survey, this focuses on the general fiures, characteristics of recent migrants (those moving to the city in the past fie years), compare to lifetime migrants (those living in the city for fie years or more) and non migrants in Tangerang. The paper also provide overview how recent migrants make adjusments on urban environments and also how recent migration has strong relationship with adolescents’ life, youth migration and empowerment.